Pelatihan Perencanaan Berbasis Data Untuk Pengawas Sekolah Temanggung Dan Pekalongan - Laily Nurlina (CV. Multi Kreasi Media, 2022)
The implementation of the independent curriculum which is the policy of the Minister of Education, Culture, Research, and Technology has a positive impact on changes in all components of education. One of the important things is data-based planning from education report cards issued by the government. School supervisors are at the forefront of changing paradigms in schools. This service in the form of training is intended for supervisors in Temanggung and Pekalongan. This training uses an online mode through the Learning Management System (LMS) and gsuite for face-to-face. Each participant was given an activeness assessment using an assessment rubric to motivate participants to be active in the discussion and training process.